Study of the Sustainable Food Yard Program among Farmer Groups in Bogor City and Cianjur Regency - Yulia Maulani; Ma’mun Sarma; Nora Herdiana Pandjaitan (Economics and Digital Business Review, 2026)
Purpose: This research aim to (1) analyze the implementation of the P2L Program in Women Farmer Groups (KWT) and Adult Farmer Groups (KTD) in Bogor City and Cianjur Regency, (2) analyze supporting and inhibiting factors affecting program success, and (3) formulate development strategies for sustainable yard management to support household food needs and income. Research Design and Methodology: A descriptive quantitative design supported by qualitative data was applied. Primary data were collected through questionnaires, interviews, expert assessment, and field observation involving 20 farmer groups/ 60 respondents, and 9 key informants. The data were analyzed using descriptive statistics, internal factor evaluation, external factor evaluation, internal-external matrix, SWOT, and Quantitative Strategic Planning Matrix. Findings and Discussion: P2L generated good to very good outcomes, although the pattern differed across regions. Bogor City performed higher in economic and socio-environmental aspects, while Cianjur Regency slightly outperformed in food security. The IFE score of 2,520 and EFE score of 2,740 positioned the program in Cell V, indicating a hold-and-maintain strategy. Implications: Sustainable P2L development requires stronger group institutions, continuous extension support, adaptive technologies, stakeholder collaboration, and market-oriented yet household-food-based product development.